Systematic Literature Review: The Impact of Working Capital Management on Profitability - Liana, Jenny; Putra, Wirmie Eka; Yuliusman, Yuliusman; Olimsar, Fredy (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to analyze and map the development of the literature on the influence of working capital management (WCM) on company profitability. The research uses the systematic literature review method with a bibliometric approach. The article selection process refers to the PRISMA guidelines through the Scopus database for the 2016–2026 period with the keywords working capital management and profitability. Of the initial 385 articles, 26 articles were obtained that met the inclusion criteria and analyzed using VOSviewer. The results of the study show that the cash conversion cycle (CCC) and its components, namely the receivables collection period, the inventory turnover period, and the trade debt payment period, are the most dominant indicators of WCM, while profitability is most proxied by return on assets (ROA). Most studies show that efficient working capital management tends to increase profitability, especially through CCC control, acceleration of receivables collection, and effective inventory management. However, some studies have also found nonlinear relationships, such as the inverted U-shape and cash threshold effect, which indicate an optimal level of working capital in maximizing profitability. In addition, the influence of WCM on profitability is influenced by sector characteristics, company size, liquidity conditions, and economic crisis situations. Based on these results, it can be concluded that WCM not only plays a role as a short-term operational policy, but also as a strategic instrument that affects the company's efficiency, profitability, and resilience.